2021
DOI: 10.1126/sciadv.abe9375
|View full text |Cite
|
Sign up to set email alerts
|

Model-guided design of mammalian genetic programs

Abstract: Genetically engineering cells to perform customizable functions is an emerging frontier with numerous technological and translational applications. However, it remains challenging to systematically engineer mammalian cells to execute complex functions. To address this need, we developed a method enabling accurate genetic program design using high-performing genetic parts and predictive computational models. We built multifunctional proteins integrating both transcriptional and posttranslational control, valida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 73 publications
2
29
0
Order By: Relevance
“…Mathematical modeling validated with experimental measurements can provide a rapid characterization of parts and a reliable prediction of circuit performance under a broad range of conditions that are challenging and costly to achieve by experiments. The success of using mathematical modeling to quantify and guide the design of synthetic gene circuits has been reported in various systems from bacteria to mammalian cells [29][30][31][32][33]. Given previous successes with model-guided design with the evaluation of the gene pulse generator and IFFL circuits [25,[34][35][36], here, we develop ordinary differential equation (ODE)-based mathematical models to first explore the capability of an RNA-only circuit functioning as an IFFL circuit for pulse generation and then, to guide the design and experimental realization of an RNA-protein hybrid IFFL circuit with predictable dynamics.…”
Section: Plasmid Construction and E Coli Strains Usedmentioning
confidence: 99%
“…Mathematical modeling validated with experimental measurements can provide a rapid characterization of parts and a reliable prediction of circuit performance under a broad range of conditions that are challenging and costly to achieve by experiments. The success of using mathematical modeling to quantify and guide the design of synthetic gene circuits has been reported in various systems from bacteria to mammalian cells [29][30][31][32][33]. Given previous successes with model-guided design with the evaluation of the gene pulse generator and IFFL circuits [25,[34][35][36], here, we develop ordinary differential equation (ODE)-based mathematical models to first explore the capability of an RNA-only circuit functioning as an IFFL circuit for pulse generation and then, to guide the design and experimental realization of an RNA-protein hybrid IFFL circuit with predictable dynamics.…”
Section: Plasmid Construction and E Coli Strains Usedmentioning
confidence: 99%
“…The most straightforward is to insert suicide genes, leading to cell death after the administration of defined molecules [ 69 ]. Alternatively, more refined ways to improve safety, control and precision based on the Boolean logic have emerged [ 70 , 71 ]. For instance, the detection of a pathological state can be improved by the dual recognition of two inducing signals, both required to trigger effector outputs: this is an AND-gate ( Figure 3 c) [ 63 , 65 ].…”
Section: Synthetic Circuit To Control Cellular Responsesmentioning
confidence: 99%
“…His group has developed mathematical models about why COMET works that have revealed quantitative design rules for building and implementing transcriptional control. Leonard showed that these rules enable predictive design of mammalian genic programs without tuning or refinement 14 …”
Section: Keynote Address: New Tools For Engineering Mammalian Cellsmentioning
confidence: 99%